Estudo térmico de pilares mistos de aço e concreto de seção tubular circular em situação de incêndio - Barcelos Filho, Carlito Botazini (2018)
Composite columns made of steel and concrete have some qualities by combining the physical and mechanical properties of the two materials. One of the advantages of using this structural element is the fire resistance when compared to steel or concrete only columns. The performance of composite columns of steel and concrete in a fire situation is influenced by some parameters such as: dimensions; slenderness; stiffness; loading; material properties and the interaction of the element with the surrounding structure. In particular about the properties of steel and concrete, they are related to the temperature that each material are submitted, because the elevation of temperature causes a decrease of properties. The objective of this research was the numerical analysis, via the finite element method using the ANSYS 17.0, the elevation of temperature in steel columns of hollow section filled with concrete of normal density, when submitted to the fire. The results show that the elevation of temperature in steel and concrete depends on parameters such as the volumes of concrete and steel, since the materials have different thermal properties. The composite columns system proved effective in decreasing the temperature of the structural element when compared to tubular steel.